2016
DOI: 10.1142/s2010194516601307
|View full text |Cite
|
Sign up to set email alerts
|

Neutron and quark stars in f(R) gravity

Abstract: The realistic compact star models are considered in f (R) gravity. The main result is that simple modified gravity can be consistent with current observational mass limit of neutron stars, with current data on their masses and radii; also, it simplifies solution of the hyperon problem. The effect of strong magnetic field in R 2 -gravity is also investigated. The existence of more compact (in comparison with General Relativity) stars with large magnetic fields in central regions is possible. In fact the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In this work, however, the mass scales are just two free parameters and we shall not consider the aforementioned values. Strange stars in R 2 gravity have also been studied in [19,20], but in the Einstein frame, while in this article we work in the Jordan frame and in the Palatini formalism. a) Starobinsky model: For a model of the form f (R) = R + R 2 /(6M 2 ) the functions we need are found to be…”
Section: Numerical Results In Two Concrete Modelsmentioning
confidence: 99%
“…In this work, however, the mass scales are just two free parameters and we shall not consider the aforementioned values. Strange stars in R 2 gravity have also been studied in [19,20], but in the Einstein frame, while in this article we work in the Jordan frame and in the Palatini formalism. a) Starobinsky model: For a model of the form f (R) = R + R 2 /(6M 2 ) the functions we need are found to be…”
Section: Numerical Results In Two Concrete Modelsmentioning
confidence: 99%
“…The first time to use a quadratic form of the Ricci scalar was given by Starobinsky [35]. It was shown that the higher-order curvature of f (R) gravity can solve the issue of the massive neutron stars [36][37][38][39][40]. It is well-known that f (R) gravity is consists of an arbitrary function whose first order is the Ricci scalar.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, a plenty of different models have been proposed to explain various other aspects of observations in astrophysics [20]. Capozziello and his collabo-rators showed that by means of Starobinsky's f (R) gravity and its higher order corrections, the problem of massive neutron stars can easily be explained [18,21,22,23,24]. Similarly, Mukhopadhyay and his collaborators also showed that these models can also explain both the classes of the white dwarfs, viz.…”
Section: Introductionmentioning
confidence: 99%